LOGISTIC WAREHOUSE INVENTORY SYSTEM (CASE STUDY: RSUD PASAR MINGGU) - Yana Iqbal Maulana; Nurul Afni; Agus Salim; Ali Haidir; Andika Bayu Hasta Yanto; Rachman Komarudin (Journal of Information System, Informatics and Computing, 2023)
The hospital is an individual health service facility that provides inpatient and outpatient care, therefore quality service is a must and absolutely fulfilled by a hospital. One of the efforts to improve the quality of service to the community is to improve the performance of the hospital in a professional and independent manner. Hospitals provide quality and effective health services to provide the best value, so that they become the first choice for all people and companies. Because logistics is so important for hospitals, the existence of an information technology-based inventory system is needed to facilitate the recording and processing of transactions compared to manual way. The problems that exist in hospitals are when checking inventory, searching for files and goods takes a long time, Logistics request forms containing requests for logistics from a unit in the hospital, and searching for logistics reports so that work in the logistics warehouse becomes less effective. To expedite the process of entering and leaving goods, a computerized system is needed that can be used to record, store, and process data to make it easier to make inventory reports. The transition from a semi-manual data archiving system to a computerized system so that the processed data is safer and easier to reuse.